Resilience and Mental Well-Being During the COVID-19 Pandemic: Serial Mediation by Persistent Thinking and Anxiety About Coronavirus - Skalski, Sebastian B.; Konaszewski, Karol; Büssing, Arndt; Surzykiewicz, Janusz (Frontiers in Psychiatry, 2022)
Reports to date indicate that the COVID-19 pandemic outbreak has negatively impacted mental health in the general population. On the other hand, positive associations of mental resilience and well-being have been widely demonstrated. The objective of this study was to assess the links between resilience (Brief Resilience Scale), persistent thinking about COVID-19 (Obsession with COVID-19 Scale), coronavirus anxiety (Coronavirus Anxiety Scale), and well-being (World Health Organization’s 5-item Well-being Index) using serial mediation. The study considered online survey data from 1,547 Poles aged 18–78 (62% of whom were women). Bootstrap sampling analysis revealed that persistent thinking about COVID-19 (M1) and coronavirus anxiety (M2) partially mediate the relationship between resilience and well-being. The results of this study indicate that persistent thinking may be dysfunctional for mental health, as it inflates pandemic anxiety and disrupts well-being. Moreover, practitioners should focus on interventions enhancing resilience in order to reduce negative mental effects during the spread of an infectious disease.